Conserved mechanism for sensor phosphatase control of two-component signaling revealed in the nitrate sensor NarX - Huynh, TuAnh Ngoc (National Academy of Sciences, 2010)
Two-component signal transduction mediates a wide range of phenotypes in microbes and plants. The sensor transmitter module controls the phosphorylation state of the cognate-response-regulator receiver domain. Whereas the two-component autokinase and phosphotransfer reactions are well-understood, the mechanism by which sensors accelerate the rate of phospho-response regulator dephosphorylation, termed “transmitter phosphatase activity,” is unknown. We identified a conserved DxxxQ motif adjacent to the phospho-accepting His residue in the HisKA_3 subfamily of two-component sensors. We used site-specific mutagenesis to make substitutions for these conserved Gln and Asp residues in the nitrate-responsive NarX sensor and analyzed function both in vivo and in vitro. Results show that the Gln residue is critical for transmitter phosphatase activity, but is not essential for autokinase or phosphotransfer activities. The documented role of an amide moiety in phosphoryl group hydrolysis suggests an analogous catalytic function for this Gln residue in HisKA_3 members. Results also indicate that the Asp residue is important for both autokinase and transmitter phosphatase activities. Furthermore, we noted that sensors of the HisKA subfamily exhibit an analogous E/DxxT/N motif, the conserved Thr residue of which is critical for transmitter phosphatase activity of the EnvZ sensor. Thus, two-component sensors likely use similar mechanisms for receiver domain dephosphorylation.